Effect of rheology and interfacial tension on spreading of emulsion drops impacting a solid surface; Physics of Fluids; Vol. 33, iss. 8 - Piskunov M. V. Maksim Vladimirovich; Semyonova A. E. Aleksandra Evgenjevna; Khomutov N. A. Nikita Andreevich; Ashikhmin A. E. Alexander Evgenjevich; Yanovsky V. A. Vyacheslav Aleksadrovich (2021, 2021)
Title screen